Parents in the Educational Management of Rural Schools - Medina-Arévalo, Adriana Del Pilar; Estupiñán-Aponte, María Rosa (Universidad Pedagógica y Tecnológica de Colombia, 2021)
As a permanent process of qualification in education, educational management addresses different aspects of the daily life of an educational establishment; therefore, it requires the contribution of all the actors that make it up. The article aims to reflect the role of parents as agents of educational management in rural school institutions in Colombia, looking to promote alternative views that recognize their contribution to improve the quality of education and the development of influence communities. For this, documents indexed in Google Academic, Dialnet, Redalyc, Latindex, Scielo, were analyzed through some searchers as: rural education, parent-school relationship, parent participation, and educational management. Considering the difficulties faced by institutions in rural contexts, parents could play a valuable role in consolidating actions that contribute to improve the quality of educational processes. In the country, the Ministry of National Education proposes to the Institutions to manage their improvement processes by articulating the members of the Educational Community, granting them the role of agents in the process, due to when linking; they contribute to the mobilization of actions promoted by the schools. However, the research on educational management in these contexts, allows to establish that rural education is being studied from its deprivations and has focused on managers and teachers where parents seen as external agents and with very low participation in the various activities that take place inside the establishments. In this way, both the family and the school continue to represent the axes of socialization of boys and girls that must be redefined from the current conditions that characterize rural contexts, to achieve more coherent and pertinent educational processes to the rural community’s needs.